On‐grid and in‐flow mixing for time‐resolved cryo‐EM. Issue 10 (4th October 2021) - Klebl, David P.; White, Howard D.; Sobott, Frank; Muench, Stephen P.
Abstract : Time‐resolved cryo‐EM allows the study of proteins under non‐equilibrium conditions on the millisecond timescale. Here, in‐flow and on‐grid mixing techniques are directly compared and it is found that on‐grid reactions can be influenced by air–water interactions, whilst in‐flow reactions give a broader distribution of reaction times due to laminar flow. Abstract : Time‐resolved cryo‐electron microscopy (TrEM) allows the study of proteins under non‐equilibrium conditions on the millisecond timescale, permitting the analysis of large‐scale conformational changes or assembly and disassembly processes. However, the technique is developing and there have been few comparisons with other biochemical kinetic studies. Using current methods, the shortest time delay is on the millisecond timescale (∼5–10 ms), given by the delay between sample application and vitrification, and generating longer time points requires additional approaches such as using a longer delay line between the mixing element and nozzle, or an incubation step on the grid. To compare approaches, the reaction of ATP with the skeletal actomyosin S1 complex was followed on grids prepared with a 7–700 ms delay between mixing and vitrification. Classification of the cryo‐EM data allows kinetic information to be derived which agrees with previous biochemical measurements, showing fast dissociation, low occupancy during steady‐state hydrolysis and rebinding once ATP has been hydrolysed. However, this rebinding effect is much less pronounced when on‐grid mixing is used and may be influenced by interactions with the air–water interface. Moreover, in‐flow mixing results in a broader distribution of reaction times due to the range of velocities in a laminar flow profile (temporal spread), especially for longer time delays. This work shows the potential of TrEM, but also highlights challenges and opportunities for further development.